Counseling on Rational Drug Use (DAGUSIBU) in Sembungan Village, Bangunjiwo, Kasihan, Bantul, D.I.Yogyakarta - Rahmat A Hi Wahid; Nurul Jannah; Fathah Dian Sari (LPPM UIKA Bogor, 2023)
Obtaining, Using, Storing and Disposal of drugs (DAGUSIBU) is part of the Drug Awareness Family Movement (GKSO) initiated by the Indonesian Pharmacist Association (IAI) in achieving understanding and awareness of the rational use of drugs. Community empowerment in Sembungan, Bangunjiwo, Kasihan, Bantul, D.I Yogyakarta hamlets aims to: (1) increase public understanding regarding the classification of drugs on the market and their differences (hard drugs, limited over-the-counter drugs, over-the-counter drugs, mandatory drug pharmacies), (2) increase public understanding regarding various types of drug preparations and how to use each to obtain the expected therapeutic effect, (3) increase public understanding regarding procedures for storing and disposing of unused drugs. This service activity uses lecture methods and interactive discussions. Before the speaker delivers the material, the respondent is given a pretest to determine the level of knowledge. While the posttest is given at the end of the delivery of the material to find out changes in knowledge. The pretest results show 64.8% (Enough). After the intervention, there was a change in the level of knowledge to 74.4% (Good). Based on these results it can be concluded that PKK cadres in Sembungan, Bangunjiwo, Kasihan, Bantul, D.I Yogyakarta have good knowledge about DAGUSIBU.